Selección varietal participativa para el mejoramiento de la yuca con agricultores en la región Caribe colombiana: Desarrollo de una metodología - López Montes, Antonio José; Hernández Romero, Luis Alfredo; Iglesias, C.A. (2007)
Farmer's participation in varietal selection has been broadly documented in several crops and countries. However, few methodological developments have focused on the development of new varieties. This paper describes a participatory varietal selection methodology (PVS) in cassava developed through a four year research project with farmers of the Colombian Caribbean region. Four phases were developed: in the diagnostic stage, farmer s practices and concepts about traits of the varieties used were queried, during the technological offer stage, 10 advanced clones provided by ICA and CIAT were selected. In the evaluation stage, a network of 60 PVS trials was established; the final stage of data processing, analysis and feed-back was developed in two phases: one of data analysis and the other incorporating the results in the plant breeding process. Whereas plant breeders chose an ideal variety based on genotypic attributes, for the farmers such a variety had a combination of biotic, physical and socio-economic characteristics. 72% of the opinions obtained during the evaluation stage referred to the root and three categories of variety acceptance were identified. Furthermore, optimal quantitative and qualitative criteria were defined for agronomic traits as well as the traits of greater importance for the farmers. Finally, using the preferred agronomic characteristics, efficacy of the selected genotypes was evaluated under six different environmental conditions (years and sites). The main outcome of this methodology was the release of four cassava varieties, the reduction from 13 to 8 years in the time to develop a variety, and, lastly, the adoption of an SVP methodology applicable in cassava breeding programs.